Karakteristik Curah Hujan Pada Lahan Gambut Kawasan Pesisir Lintang Utara Dan Selatan Kalimantan Barat - Suryadi, Urai Edi; Chandra, Tino O; Krisnohadi, Ari (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2025)
The peatland of the Coastal Area is wider than the Inland Area of West Kalimantan Province, where the peatland of the Coastal Area South Latitude is wider than North Latitude. This study aims to examine the characteristics of rainfall that occurs in the Coastal Area of the Regency/City of North Latitude and South Latitude of West Kalimantan Province which is the basis for planning sustainable peatland management. The research method analyzes the characteristics of rainfall at 4 climatology stations with the furthest and closest distances to the Equator in the Coastal Area of West Kalimantan North Latitude (Sambas and Mempawan) and South Latitude (Kubu Raya and Ketapang). The results of the study show that Climate Type A (Very Wet) except Ketapang has Climate Type B (Wet), a return period (Tr) of 2 years and a 50% chance is a very important design plan on rainfall and minimum monthly rainy days as a basis for planning water management for water management to anticipate drought on cultivated land and dry peat soil that does not return, on rainfall and maximum monthly rainy days as a basis for planning water management for land drainage to anticipate excess water that can disrupt the growth of cultivated plants, as well as a return period (Tr) of 20 years and a 5% chance (P) is a very recommended design plan on maximum daily rainfall as a basis for planning location-specific water channels so that the land does not experience flooding and drought for sustainable water management of cultivated peatland plants